Вредносниот систем на менаџерите и развојот на човечките ресурси во претпријатијата - Есмерова, Емануела (Економски факултет, УКИМ, Скопје, 2014)
The managers’ system of values is comprised of the values they own, some of which are genetic and some are acquired with tendency to use them. The personal values determine the personality itself, its capabilities, characteristics, moral and authority. The values through the system of values give a description of managers’ work and what they think, considering their behavior through their working activities. Through the empiric research we can identify the values used and preferred by the managers, their system of values from aspect of the interviewed managers from one side, and the interviewed employees from another. The aim is to find out their influence on the development of the employees’ human resources. Values are reflection of our awareness of life, of relationships between people and the actions we take through our life situations. They show our opinion about what is good and right and what is bad and wrong. The development of human resources is of great importance to the strategic advantage of enterprises in the competitive market struggle, which should not be left on their own, neither to the personal judgment and initiative of individuals. It also should be well organized and run by the management team of enterprises. Since the development of human resources management, the managers obtain all the necessary skills, experience and attitudes in oreder to be successful in their businesses. Training is a continuous process of enrichment, extension and refinement of knowledge, skills and behavior of the human resources that will contribute to better and more efficient performance of the work at the work place and in practice. The mentorship enables employees (mentored) with assistance in the development and promotion of their businesses, and on the other hand it enables to gain the quality knowledge from their mentors and additional skills and partnerships. The inclusion in the mentoring team means that mentors have the opportunity to promote their work and achieved success in business and management. Education through the process of training is internationally and systematically designed and organized teaching system and learning experience of the individuals which can be seen and presented in the growth of knowledge and skills (as in quality and quantity) and also in the development of capabilities of those individuals. Market, international and modern economy provides managers with good vision and strategy a chance to build a good value system, to engage themselves in the competitive struggle on the international market, to increase motivation and satisfaction of employees and to succeed in achieving satisfaction, cooperation with business partners, customers and users of services and to implement and operate a system of values with the right and required values.
Value manager’s system and human resource development in the enterprises
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: management, resources, development, human resources, training, enterprises